Ricerche sul Corpus del parlato romanzo C-ORAL-ROM Studi linguistici e applicazioni didattiche per l'insegnamento di L2 - María Carlota Nicolás Martínez (Electronica, 2007)
This book is the first initiative of its kind aimed at underscoring the importance of the C-ORAL-ROM project, and proposing new methods of utilisation and study of the corpora comprised within it, especially in the framework of language teaching. The objective of the project is that of creating a corpus of the spontaneous spoken language for the principal Romance languages: French, Italian, Portuguese and Spanish. The publication includes both written and audio texts, considered as the most appropriate manner of utilising and studying the oral corpora. The texts of the authors hosted in the volume dwell on the various aspects that enable C-ORAL-ROM to be used as a container of information, as a teaching instrument and also as a means of analysing the formal, structural and prosodic characteristics of the texts. The last part of the book presents a teaching unit that proposes a direct application to the teaching of the oral corpora.